(3GdLhGH GdfGWb HGdUhGH GdbGWY dYQi GdTc hGdGQJjGHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO Gddg GdPi CfWb dSGf GdHQgGf HMGdg , aJajCfG ai eMOhO XdGdg , hcQYfG ai fejQ SdSGdg , hChQOfG ehGQO GdfXQ s
(3BNQgG (B:s
(3hajg HMK Objb jdjb ESJbUGDg HGdcJH GdcdGejI , hbO PcQfGg ai cJHfG GdYbdjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG HYV GdJYdjbGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds